Enhanced Hydrogen Production by the Halotolerant Cyanobacterium Aphanothece halophytica Through Bacterial Co-Cultivation - Chutikarn Somsin; Nattanon Chinchusak; Aran Incharoensakdi; Saranya Phunpruch (Fermentation, 2026)
Hydrogen (H2) is a promising clean energy carrier with the potential to partially replace fossil fuels. Biological H2 production using microorganisms offers an environmentally friendly alternative. The halotolerant cyanobacterium Aphanothece halophytica can produce H2 under nitrogen-deprived and dark anaerobic conditions. In this study, a co-culture strategy was investigated to enhance H2 production. Five bacterial strains were screened for their ability to improve H2 production when co-cultivated with A. halophytica. Among them, Staphylococcus aureus significantly enhanced H2 production, achieving a maximum rate of 11.11 ± 0.18 µmol H2 g−1 dry weight h−1. Optimization of the bacterial partner revealed that S. aureus cells harvested at 12 h in the mid-logarithmic phase with an OD600 of 4.0 were the most effective. An inoculum ratio of A. halophytica to S. aureus of 4:1 further enhanced H2 production, increased bidirectional hydrogenase activity, and reduced O2 accumulation. Under optimal conditions (0.945 mmol C-atom L−1 glucose, 0.25 M NaCl, pH 7.4, and 35 °C), the maximum H2 production rate reached 132.49 ± 4.45 µmol H2 g−1 dry weight h−1, approximately 5.5-fold higher than that under normal conditions. The co-culture achieved a cumulative H2 yield of 3248.51 ± 88.11 µmol H2 g−1 dry weight after 48 h.
Keywords: Anaerobic Digestion and Biogas Production; Microbial metabolism and enzyme function; Algal biology and biofuel production